3573 Critical Barriers to Effective Community-Academic Research Partnerships and Potential Solutions - Woolford, Susan J (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: Background: The importance of engaging community in research and fostering community-academic research partnerships is increasingly acknowledged by Clinical and Translational Science Award (CTSA) institutes. However, forming and maintaining such collaborations is often hampered by numerous challenges. It is critical to investigate the barriers to effective community-academic partnerships and to develop novel approaches to overcome these barriers. Objective: To explore community and academic perspectives of the challenges faced by community-academic research partnerships and potential solutions to these identified challenges. METHODS/STUDY POPULATION: Methods: In an effort to explore creative approaches to address these issues, the Community Engagement Program at the Michigan Institute for Clinical & Health Research (MICHR), the CTSA site that serves Michigan, hosted a retreat to elicit the input of community members and academics from across the state. There was a mix of participants ranging from those with established community-academic partnerships to others who were new to community-engaged research and in early stages of forming partnerships. At the retreat, attendees were randomly divided into groups and asked to answer the specific question, “What are your barriers to partnering in research?” After each group identified a set of barriers and reported their findings to the entire room, attendees were asked to work again in their small groups to discuss potential solutions to these barriers. Ideas for solutions were also shared with the entire room. As part of the process of brainstorming about these questions, attendees were asked to document their ideas --- for both barriers and solutions --- on post-it notes which were then grouped by category. Artifacts from the retreat were saved digitally and transcripts made from these records. The findings were then analyzed to identify common themes. RESULTS/ANTICIPATED RESULTS: Results: Eighty-six participants attended the retreat from across the state of Michigan. Forty-three represented community organizations that focus on addressing a wide array of social determinants of health issues. The remaining forty-three participants represented various academic institutions. The most frequently mentioned challenges to community-academic partnerships were related to communication and relationship building. To overcome barriers in these areas, participants noted that it is critical to collaboratively and explicitly identify shared goals, values and norms in the early stages of partnership development. This was closely linked to the need for additional funding to help foster and strengthen relationships by allowing partners to spend time together to both work and socialize informally, preferably in face-to-face settings. These were deemed crucial for building trust and common ground. In addition, more equitable funding and role distribution --- including shared leadership and governance of research projects between community and academia--- that recognizes and supports the true costs of involvement in research for community members was viewed as important. Other frequently noted issues on the part of community members were the need for greater respect for community partners and for more training opportunities to build capacity within communities to participate in research. Participants from academic institutions emphasized that the current requirements and timeline for promotion in academia make it harder for them to participate in community-engaged research, especially as early career researchers. They maintained that wider recognition of the value of community-engaged research is necessary and that this requires the support of home departments. Finally, participants underscored the importance of building infrastructure to better connect potential partners from the community and academia by making it easier to identify common interests and reciprocal strengths. DISCUSSION/SIGNIFICANCE OF IMPACT: Conclusion: The problems faced by community-academic partnerships may be alleviated by working with community and academic members to identify potential solutions. Further work is needed to systematically examine barriers and the efficacy of solutions to enhance community-academic partnerships. Acknowledgements: We thank all attendees of the MICHR Community Engagement retreat for their participation in this activity that explored barriers to effective community-academic partnerships. Their honest and frank feedback was essential to broaching sensitive topics related to partnership development, and to identify realistic and practical solutions. We also thank all members of the planning committee and our colleagues in the Community Engagement Program for their work on bringing together community and academic members for this retreat. This project was supported by grant number UL1TR002240 from the National Center for Advancing Translational Sciences (NCATS).